The Effect of Captioned versus Non-Captioned Extensive Listening on the Listening Fluency of EFL Pre-Service Teachers - Rozak, Refi Ranto; Fadillah, Dewi Nur Isnaini (LPPM Universitas Hasyim Asy'ari Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This article reports on a quasi-experimental, embedded mixed-methods study that examined whether, and for whom, captioned and non-captioned extensive listening (EL) differentially affect the listening fluency (LF) of English as a foreign language (EFL) pre-service teachers, while attending to the moderating role of foreign language listening anxiety (FLLA). A total of 126 third-semester student teachers at two private universities in East Java, Indonesia, were classified into high- and low-FLLA groups by means of Kim’s (2000) Foreign Language Listening Anxiety Scale and taught across a fourteen-week treatment, with a listening fluency test delivered at 160 words per minute administered before and after the intervention. Paired-samples and independent-samples t-tests, together with a two-way analysis of variance, indicated that captioned EL produced statistically significant gains for both anxiety groups, whereas non-captioned EL benefited only low-FLLA learners; a significant interaction (p = .028) revealed that the effect of input mode was contingent upon the learners’ anxiety level. Qualitative data drawn from perception surveys, observation, and interviews further suggested that captions functioned as a compensatory scaffold that supported word recognition and mitigated anxiety. Three pedagogical implications are advanced, and further investigative endeavor into captioned EL in EFL teacher education is invited.